Advances in fruit breeding in Nepal - Gotame, Tek P; Gautam, Ishwori P; Shrestha, Surendra L; Shrestha, Jiban; Joshi, Bal Krishna (Journal of Agriculture and Natural Resources, 2020)
Nepal has spent about six decades on fruit development and research in different species. Fruit breeding particularly local and exotic germplasm collection started after 1950s and has gained momentum after the formation of commodity programme in 1972 AD. Major researches in the past were focused on indigenous and exotic genotype collection, evaluation, selection, propagation protocol standardization and adoptive trials. Some good ground works have already been done in major fruits such as apple, pear, plum, persimmon, kiwifruit, citrus, litchi, guava, pomegranate, walnut, papaya, banana and mango. The major public institutions involved in fruit breeding are Nepal Agricultural Research Council (NARC) following Agriculture and Forestry University. Some of the private nurseries like Everything Organic Nursery, Kavre and Technology Demonstration Centre of ICIMOD, Lalitpur were also involved in introduction and maintenance of indigenous and exotic fruit species. National Centre for Fruit Development, Kirtipur; Tropical Region Horticulture Centre, Nawalpur; Temperate Horticulture Farm, Satbanj, and Horticulture Farm, Marpha collected many local and exotic fruits and maintained at field gene bank. Horticulture Research Station, Rajikot has introduced 25 spur type apple cultivars and maintained in field gene bank. National Citrus Research Programme, Paripatle has introduced, collected and maintained 130 genotypes including exotic and indigenous landraces of citrus. Two varieties of acid lime ‘Sunkagati-1’ and ‘Sunkagati-2’ have been released and one variety ‘Terhathum Local’ has been registered. ‘Khoku Selection’ of mandarin orange has also been registered. Banana varieties 'Malbhog', 'Willium Hybrid' and 'G9' has been selected by participatory varietal selection and registered. To strengthen fruit breeding in the nation, NARC needs to be restructured with special focus on fruit researches. Establishment of national fruit commodity programs along with establishment of Tropical Fruit Research Station in Province 2 and Temperate Fruit Research Station in Province 5 at national level can streamline NARC's fruit breeding researches.